Characteristics of Low Back Pain Patients at The West Aceh Health Center for The Period January 2022 - June 2023 - Adico Notareza Aulia; Safrizal Rahman; Laila Apriani Hasanah Harahap (Universitas Airlangga, 2023)
Background: Around the world, 80% of adults experience low back pain (LBP). LBP frequently results in disability in sufferers, which affects many facets of life. We conducted this study to ascertain the prevalence of low back pain cases in the general clinic of health centers in West Aceh Regency due to the rising incidence of LBP in the world.Methods: To identify the characteristics of LBP (Low Back Pain) patients in the general clinic of health centers in West Aceh Regency from January to June 2023, we utilized a descriptive study approach with a cross-sectional design. Purposive and non-probability sampling were used in this study's sampling procedures.Results: From January 2022 to June 2023, 21.600 patients were registered for care at the general clinic of the health centers in the West Aceh area. 230 LBP patients were diagnosed during that time, or 10,6 cases per every 1000 clinic visits.Conclusion: The results showed that LBP patients who came to the General Clinic of the West Aceh Health Center from January 2022 to June 2023 were mostly in the age group 50-60 years. Namely, 112 samples (48.7%), female gender 140 people (60.9%) and male 90 people (39.1%), and the type of work patients who experience the most LBP are housewives, as many as 61 people from the total sample.